Halloween [videorecording (DVD)] - Carpenter, John, 1948- (Shout! Factory, 2021)
Halloween night. A young Michael Myers butchers his older sister with a kitchen knife. Fifteen years later, he escapes from a mental institution only to return home and terrorize the town and babysitter Laurie.